Hypochondriasis and health anxiety : a guide for clinicians - Starcevic, Vladan; Noyes, Russell, Jr (Oxford University Press, 2014)
This text is a state-of-the-art resource and essential guide to hypochondriasis and illness anxiety for clinicians, mental health professionals, and general medical practitioners. Using a pragmatic approach, it offers a wealth of clinically useful information. The book also provides a critical review of the underlying conceptual and treatment issues, addressing varying perspectives and synthesizing the current research.